Pembelajaran Al Quran Model Cinta Konsep CIRC Pondok Ilmu - Amaliyah, Amaliyah; Merdeka, Muhamad (Jurnal PKM Manajemen Bisnis, 2024)
The Qur'an revealed by Allah SWT is a guide and guidance for humans. This is because the AI-Quran has the values ​​of guidance, guidance and glory in its substance, all of which must be maintained and guarded properly. A person must not forget the Koran, let alone turn his back on it or abandon it. The Qur'an contains several essences such as kalaamullaah, miracles, was revealed to the heart of the prophet, was conveyed mutawtir and reading it is worship. So that the Qur'an provides light for readers. To be able to produce successful learning, the Islamic boarding school uses the CIRC concept of love model, which is expected to fulfill the achievement of feeling the miracle of the Koran when reading it, feeling the energy that enters the mind, heart & body, feeling syifa (medicine) for the body & spiritual, the light of the Qur'an for a way of life in the world.